Gastric insufflation during cardiopulmonary resuscitation: A study in human cadavers. (1st January 2020) - Savary, Dominique; Drennan, Ian R.; Badat, Bilal; Grieco, Domenico L.; Piraino, Thomas; Lesimple, Arnaud; Charbonney, Emmanuel; Fritz, Caroline; Delisle, Stephane; Ouellet, Paul; Mercat, Alain; Bronchti, Gilles; et al.
Abstract: Introduction: Bag-valve-mask ventilation is the first-line ventilation method during cardiopulmonary resuscitation (CPR). Risks include excessive volume delivery and gastric insufflation, the latter increasing the risk of pneumonia. The efficacy of ventilation can also be reduced by airway closure. We hypothesized that continuous chest compression (CC) could limit the risk of gastric insufflation compared to the recommended 30:2 interrupted CC strategy. This experimental study was performed in human "Thiel" cadavers to assess the respective impact of discontinuous vs. continuous chest compressions on gastric insufflation and ventilation during CPR. Methods: The 30:2 interrupted CC technique was compared to continuous CC in 5 non-intubated cadavers over a 6 min-period. Flow and Airway Pressure were measured at the mask. A percutaneous gastrostomy allowed measuring the cumulative gastric insufflated volume. Two additional cadavers were equipped with esophageal and gastric catheters instead of the gastrostomy. Results: For the 7 cadavers studied (4 women) median age of death was 79 [74–84] years. After 6 min of CPR, the cumulative gastric insufflation measured in 5 cadavers was markedly reduced during continuous CC compared to the interrupted CC strategy: (1.0 [0.8–4.1] vs. 5.9 [4.0–5.6] L; p < 0.05) while expired minute ventilation was slightly higher during continuous than interrupted CC (1.9 [1.4–2.8] vs. 1.6 [1.1–2.7] L/min; P < 0.05). In 2 additional cadavers, the progressive rise in baseline gastric pressure was lower during continuous CC than interrupted CC (1 and 2 cmH2 O vs. 12 and 5.8 cmH2 O). Conclusion: Continuous CC significantly reduces the volume of gas insufflated in the stomach compared to the recommended 30:2 interrupted CC strategy. Ventilation actually delivered to the lung is also slightly increased by the strategy.